2019
DOI: 10.1039/c9ra03866c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a high-surface area V2O5/TiO2–SiO2catalyst and its application in the visible light photocatalytic degradation of methylene blue

Abstract: In the present study, we synthesized several high-surface area V2O5/TiO2–SiO2 catalysts (vanado titanium silicate, VTS). The synthesized materials are characterized by PXRD, FE-SEM/EDAX, TEM, BET-surface area, FT-IR, UV-Vis, XPS, fluorescence and photocatalytic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Furthermore, the presence of V 4+ , as evidenced by the XPS result in our work, supports and provides the higher active sites. It also provides high electrical conductivity, leading to boosting the separation and transfer of photogenerated charge carriers, which is important for photocatalytic reactions, as reported previously [ 39 , 40 , 41 , 42 ]. In this process, it was indicated that photoelectrons and holes were well separated and their recombinations were reduced.…”
Section: Resultsmentioning
confidence: 64%
“…Furthermore, the presence of V 4+ , as evidenced by the XPS result in our work, supports and provides the higher active sites. It also provides high electrical conductivity, leading to boosting the separation and transfer of photogenerated charge carriers, which is important for photocatalytic reactions, as reported previously [ 39 , 40 , 41 , 42 ]. In this process, it was indicated that photoelectrons and holes were well separated and their recombinations were reduced.…”
Section: Resultsmentioning
confidence: 64%
“…5 b,c). From the results, all prepared films produced under magnetic field had prominent photocatalytic performances over the TV sample possibly due to their narrowed bandgap, re-crystallization, high porosity, and the strongly interface between TiO 2 and V 2 O 5 nanoparticles 30 , 31 . Unbelievable, the TVH sample provide great photocatalytic efficiency than post-annealed TVA sample.…”
Section: Resultsmentioning
confidence: 98%
“…These images highlight the successful distribution of both Fe and dopant nanoparticles on the BC surface. The closely packed surface morphology of the prepared BC composite photocatalyst is significant, as it supports efficient charge carrier separation [30]. The proximity between the photocatalyst and BC, acting as a substrate and an electron sink, is advantageous for prolonging the photocatalytic activation of the composite photocatalyst.…”
Section: Characterization Of Catalystmentioning
confidence: 99%